The future of Russian-Ukrainian relations (International Seven Journal of Multidisciplinary, 2023)
This article explores the intricate relations between Russia and Ukraine, emphasizing potential paths for the future and the variables that could influence their evolution. Starting with the annexation of Crimea in 2014, the scenario has become increasingly complex with conflicts in Donetsk and Luhansk, raising questions about Ukraine's territorial integrity and continued quest for self-determination. The role of external powers, energy interdependence and the challenges of disinformation are analyzed to understand their implications for bilateral relations. The Minsk Agreements, as diplomatic milestones, demonstrate the need for renewed or complementary approaches to sustainable peace. Additionally, Ukraine's cultural and linguistic identity, amid geopolitical tensions, emerges as a central element in defining its geopolitical future. The article concludes that resolving the conflict and strengthening relations will depend on a mutual commitment to dialogue, consideration of popular aspirations and a balanced understanding of the geopolitical interests at stake.